Undifferentiated connective tissue disease with an incidental photo-provocation: a case report - Roofeh, David; Kahlenberg, J. Michelle (Frontiers in Lupus, 2023)
A patient with undifferentiated connective tissue disease and no documented history of photosensitivity 6 fastidiously adhered to the rheumatologist's recommendation to avoid UV light exposure. Her unexpected UV 7 exposure revealed the development of multiple erythematous/violaceous macules, concerning for a cutaneous 8 lupus erythematosus reaction with an appearance similar to chilblains. This case highlights the importance of 9 screening for unintentional photo-provocation in those suspected to have or be at risk for developing systemic 10 lupus erythematosus (SLE).